Phenotypic characterization and antimicrobial resistance of Campylobacter jejuni and Campylobacter coli in broiler chickens and slaughterhouse workers in Algeria - Messaoudene, Hakima; Guessoum, Meryem; Heleili, Nouzha; Ayachi, Ammar (Journal of Advanced Veterinary and Animal Research, 2025)
Objectives: This study assessed the prevalence, phenotypic antimicrobial resistance profiles, and multidrug resistance patterns of Campylobacter jejuni (C. jejuni) and Campylobacter coli (C. coli) isolated from broiler chickens and slaughterhouse workers in Algeria to craft One Health strategies. Material and Methods: Samples were collected from poultry carcasses (n = 300) and slaughterhouse workers (n = 133). Campylobacter spp. were isolated and identified using classical phenotypic microbiological methods, followed by antimicrobial susceptibility testing to assess resistance patterns, including MDR profiles. Results: Campylobacter spp. were detected in 66.3% of samples, with the highest prevalence in caeca (96%) and cloacal swabs (70%), while lower rates were observed in neck skin (33%). Among slaughterhouse workers, Campylobacter was detected in 3.9% of samples from workers in semi-industrial settings and in 5.9% of hand scrapings. Campylobacter jejuni was the predominant species (29%), followed by C. coli (11.3%). High resistance rates were observed against ciprofloxacin (82.6% in C. jejuni, 58% in C. coli) and tetracycline (48% in C. jejuni). Workers’ isolates exhibited 100% resistance to ampicillin, with moderate resistance to other antibiotics. Multidrug resistance was most frequently observed in C. jejuni, particularly against ciprofloxacin, tetracycline, and erythromycin. Conclusion: These findings underscore poultry as critical reservoirs of thermotolerant Campylobacter and the urgent need for a coordinated One Health approach, which is vital to minimize the risk of bacterial transmission and Campylobacter infections, as well as to combat antibiotic resistance. This approach integrates surveillance and control measures to address the interconnection between human, animal, and environmental health in Algeria. J. Adv. Vet. Anim. Res., 12(3): 908–915, September 2025 http://doi.org/10.5455/javar.2025.l952